Peran Pemerintah Daerah Kota Bekasi Dalam Mewujudkan Penataan Ruang Terbuka Hijau - Cahyo, Reza Dwi; Susanti, Martien Herna; Sunarto, Sunarto (Unnes Political Science Journal, 2017)
The city of Bekasi, including one of the city are hard to do development in all areas, including the revamping of the city. The problem of green open space in Bekasi of particular, require the handling of the structurally through various studies and policy given the green open a remote ecosystem a particular environment for the area being developed. There needs to be the role of local goverments in realizing the arrangement of green open space in Bekasi City. The formulation of the problem of this study is. 1) If the efforts made by the city of Bekasi in the realization of green open space?, 2) How public participation in the realization of green open space in the city of Bekasi?, 3) Factors are to be an obstacle to the local government in pursuit of green open space in the city of Bekasi? The study with the qualitative. The research at the center of the city of Bekasi and the public city of Bekasi. An informant for the research is staff BAPPEDA the city of Bekasi, staff official city planning of Bekasi city and society. Focus of research which is 1) Local goverments, 2) Public participation, 3) Factors in the opposite direction. Techniques of collecting data in an observation, interviews, and documentation. Technical analysis includes data collection, the reduction of data, the presentation of data, and the withdrawal of the conlusion. The results showed that: 1) The city of Bekasi set the location decided by the mayor of Bekasi through the regulations of the mayor of Bekasi number 5 year 2015 of the way the provision of incentives and disincentives in the control of the utilization of space in the city of Bekasi, local government provides incentives to people who are encouraged to do the use of green open space in the city of Bekasi. 2) Forms of public participation submitted to the local government city of Bekasi in oral or written and delivered to the department of related with counseling and guidance of green open space, a campaign of green open space through the mass media and electronics, making the green school and green campus, the fulfillment of the open green space, community organizations and the award to the public has a green open space. 3) Public awareness in the provision of green open space, there are still obstacles both obstacles the internal and external constraints, obstacles internally by the constraints the government and external problems is the constraint of the community people. Advice : 1) There needs to be the program and activites that are more about green open space itself as weel as socialize the program has been made so that people can understand a program for local governments, 2) For the people there should be a concern about the green open space to the creation of a comfortable, environment and clean, 3) The city of Bekasi to disseminate green open space to the community by providing knowledge about the importance of achieving green open space through regional regulation in order to create awareness of people that can preserve and maintain green open space in the city of Bekasi